Análise da cobertura vacinal da vacina quadrivalente contra o HPV no Município de Curitiba entre os anos de 2014 e 2019 - Kupczak, Giovana e Silva (2021)
INTRODUCTION: The human papillomavirus is the main causative agent of cervical cancer, which is the fourth leading cause of cancer death in women in Brazil, besides causing cancer at other sites. In Brazil, quadrivalent HPV vaccine is available, and is given as a two-dose regimen in females aged 9 to 14 years and males aged 11 to 14 years, and as a three-dose regimen in immunosuppressed females aged 9 to 45 years and immunosuppressed males aged 9 to 26 years. The goal of HPV vaccine coverage is 80%, and it is essential to achieve this coverage to reduce morbidity and mortality from HPV in the municipality. The paper’s objective is to present and discuss the vaccination profile of the quadrivalent HPV vaccine in the city of Curitiba from 2014 to 2019. METHODS: Ecological type observational study conducted by collecting vaccine data from the Epidemiology sector of the Municipal Health Department of Curitiba-PR, in the period from 2014 to 2019. Information from HPV vaccine administrations (1st, 2nd and 3rd doses) in people of both genders aged between 9 and 88 years was collected. RESULTS: In the period studied, 310,861 doses of HPV vaccine were administered in Curitiba, 176,022 (56.6%) corresponding to the first dose, 120,784 (38.8%) to the second dose, and 8,530 (2.7%) to the third dose. Of this total, 260,033 doses were administered in the target age group. After the inclusion of men in the vaccination scheme, in 2017, 100,885 doses were administered in this population, which had a coverage of the target age group of 65.4% in the first dose and 37.1% in the second dose. In the period, the coverage of the female public was 88.2% in the first dose and 59.2% in the second dose. In the target population in general, the coverage was 76.2% in the first dose and 50.8% in the second one. CONCLUSION: Females are more adherent to immunization when compared to males, but both present low coverage for the second dose, so that educational measures and active search of the population are needed for the vaccination scheme to be completed and the population's immunization is achieved to decrease morbidity and mortality from HPV.